THE POET'S SKILL OF MAKING FUNNY SITUATIONS - Ravshanova Gulruxbegim Qahramon qizi (Journals Park Publishing, 2022)
Laughter is the most powerful weapon of satire, the satirical writer. What also devalues a satirical work is that it lacks laughter. The magic, charm, and charm of any work of art, including comics, depend on the language of the work of art. People's writer Pirimkul Kadyrov said: “The power and advantages of any language will develop and grow only if the people who created it live together. A language cut off from its people and land begins to lose its natural power, richness and beauty. So, there is a hand, there is a tongue. A person who is not cut off from the hand does not lose his tongue, ”he said.Indeed, if we look at Abdulla Aripov's comedy from this point of view, the poet is a creator who has mastered the language of the people, the ability to describe the suffering of the people in an international way. Although satirical laughter predominates in the poet's comedy, it is clear that at the heart of this laughter is a strong desire to improve the lives of the people, to enrich their spirituality.